Evaluating the investment performance of Japanese households: A comparison between professional financial advice and free financial advice - Yoshihiko Kadoya; Sumeet Lal; Jin Shinohara; Mostafa Saidur Rahim Khan (Heliyon)
Technological advancements have given rise to various sources of financial advice, prompting an investigation into how professional and free financial advice influence investment performance. Research lacks clarity on the impact of professional services on investment performance and overlooks the potential of free financial advice. This study, analyzing data from Rakuten Securities, a leading online-based security company in Japan, finds that investors prefer free financial advice from sources such as social media, mass media, personal networks, and individual decision-making. Regression analysis reveals that investors utilizing free financial advice from their account-holding securities company, social media, mass media, and personal networks show better investment performance than those relying on professional advice. This emphasizes a shift in investor behavior. While it is known that professional advice can lead to subpar results, our study provides new evidence that free financial advice can improve investment performance. The results suggest that professional advisors should emphasize the uniqueness and added value of their services to attract investors, particularly given the prevalence of freely available alternatives.